CULTURAL CAPSULES AND READING TEXTS: TRIGGERS TO CROSS-CULTURAL LANGUAGE AWARENESS - Maya Khemlani David (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
The use of English in the international setting is based on cultural presuppositions about the kinds of language performance that are appropriate for specific situations. Culture capsules are useful teaching techniques to teach English, as learners would be able to bring in their own cultural insights into learning the pragmatics of English through the various combinations of word choice, prosodic and paralinguistic features. This paper will provide examples of capsules which focus on a range of speech acts (greetings, directives, requests, etc) and demonstrate how they can be used as a stimulus to cross-cultural language awareness.